2011
DOI: 10.1163/092050610x538218
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silk Fibroin Film as a Transparent Carrier for Cultivated Corneal Epithelial Sheets

Abstract: Biological carriers, such as the amniotic membrane and serum-derived fibrin, are currently used to deliver cultivated corneal epithelial sheets to the ocular surface. Such carriers require being transparent and allowing the diffusion of metabolites in order to maintain a healthy ocular surface. However, safety issues concerning biological agents encouraged the development of safer, biocompatible materials as cell carriers. We examined the application of porous silk fibroin films with high molecular permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 33 publications
7
63
0
1
Order By: Relevance
“…Clinical slit-lamp observations showed that the material maintained good transparency over the 90-day period of observation. Our data are in agreement with the previously published study by Vieira et al 29 and Higa et al 30 in which 2 or 5-mm diameter single-layer silk films, respectively, were used.…”
Section: Discussionsupporting
confidence: 94%
“…Clinical slit-lamp observations showed that the material maintained good transparency over the 90-day period of observation. Our data are in agreement with the previously published study by Vieira et al 29 and Higa et al 30 in which 2 or 5-mm diameter single-layer silk films, respectively, were used.…”
Section: Discussionsupporting
confidence: 94%
“…Results from our own preliminary studies using a rabbit model indicate that 2-mm discs cut from fibroin films are well tolerated when implanted within the central corneal stroma, with little evidence of leukocyte recruitment or fibroblast proliferation being observed over 60 days [71]. A similar result has recently been reported by Higa et al [61] using 5-mm fibroin film discs. Nevertheless, both results may well have been influenced by the avascular nature of the central cornea.…”
Section: Questions That Require Further Investigationsupporting
confidence: 69%
“…Traditionally, 3T3 fibroblast cell lines established from mouse embryos are used for this purpose, but a number of recent studies including those by our own group have shown that primary cultures of human limbal fibroblasts can also be used [31]. At time of submitting this paper, a detailed study by Higa et al has just appeared in press [61] characterising the phenotype of rabbit primary corneolimbal epithelial cells when grown on fibroin films mounted above a 3T3 feeder layer by using a porous cell culture insert. Two particularly important observations are made in this study.…”
Section: Prior Studies Of Ocular Cell Responses To Fibroinmentioning
confidence: 99%
“…While little of the native full-length protein remains following processing, the resulting peptide solutions can subsequently be used to generate a variety of stable and biocompatible materials including freestanding membranes, electro-spun fibers and porous sponges [24]. Of these three materials, the freestanding BMSF membranes have received most attention for potential use in corneal tissue reconstruction owing to their high degree of transparency and general handling properties [25][26][27][28]. Importantly, subsequent studies have revealed that BMSF-based materials support the attachment, growth and differentiation of cells isolated from all three main tissue layers of the cornea [25,[28][29][30].…”
Section: • Silk Fibroin Based Constructsmentioning
confidence: 99%
“…Theoretically, combining these approaches could lead to creation of a full-thickness corneal tissue substitute as described in Figure 1. Preliminary studies by Higa et al [27] indicate that single BMSFmembranes are well tolerated when implanted within the corneal stroma, but safety and efficacy data for of any combination of cells grown on BMSF membranes has yet to be reported.…”
Section: • Silk Fibroin Based Constructsmentioning
confidence: 99%